Uropathogenic Escherichia coli virulence factor hemolysin A causes programmed cell necrosis by altering mitochondrial dynamics. Issue 8 (28th February 2018) - Lu, Yongning; Rafiq, Amir; Zhang, Zhengguo; Aslani, Ferial; Fijak, Monika; Lei, Tao; Wang, Ming; Kumar, Sanjeev; Klug, Jörg; Bergmann, Martin; Chakraborty, Trinad; Meinhardt, Andreas; et al.
Abstract : Uropathogenic Escherichia coli (UPEC) is the most common cause of urinary tract infections. In this study, UPEC strains harboring hemolysin A (HlyA) did not induce programmed cell death pathways by the activation of caspases. Instead, the UPEC pore‐forming toxin HlyA triggered an increase in mitochondrial Ca 2+ levels and manipulated mitochondrial dynamics by causing fragmentation of the mitochondrial network. Alterations in mi‐tochondrial dynamics resulted in severe impairment of mitochondrial functions by loss of membrane potential, increase in reactive oxygen species production, and ATP depletion. Moreover, HlyA caused disruption of plasma membrane integrity that was accompanied by extracellular release of the danger‐associated molecules high‐mobility group box 1 (HMGB1) and histone 3 (H3). Our results indicate that UPEC induced programmed cell necrosis by irreversibly impairing mitochondrial function. This finding suggests a strategy devised by UPEC at the onset of infection to escape early innate immune response and silently propagate inside host cells.—Lu, Y., Rafiq, A., Zhang, Z., Aslani, F., Fijak, M., Lei, T., Wang, M., Kumar, S., Klug, J., Bergmann, M., Chakraborty, T., Meinhardt, A., Bhushan, S. Uropathogenic Escherichia coli virulence factor hemolysin A causes programmed cell necrosis by altering mitochondrial dynamics. FASEB J . 32, 4107–4120 (2018). www.fasebj.org